Exploring students’ view of using Google Docs in writing class - Fahmi Hidayat (Universitas Bengkulu, 2020)
The purpose of this study was to explore what do students really think about using google docs for peer feedback? the potential of Google Documents in facilitating and supporting pedagogical practices in a writing course at Higher Education level. In this qualitative case study, it was carried out among 34 students that working in pairs on article report writing over one academic semester. At the end of the semester, students were interviewed and the results were qualitatively analyzed. The findings show what do students feel that they are effectively tooled in helping them write a report. Is there a difference of opinion about Google Documents using outside of the classroom and traditional course?